THE AESTHETICS OF KORI KUWADI - I Wayan Balika Ika; Putu Ari Darmastuti (Journal of Aesthetics, Design, and Art Management, 2022)
Purpose: As one of the objects of Balinese cultural heritage, it should be preserved. But in reality, Kori Kuwadi is exploited not only as a building component but also as a commodity that is traded and even exported to foreign countries. To obtain maximum profit, Kori Kuwadi is mass-produced to meet market demand. Because it is oriented towards high profits, the production process may ignore the Kori Kuwadi concept as it should. Ironic while the existence of Kori Kuwadi is widely known both by the Balinese people and the people outside Bali, because the shape, model, size, and ornament are so beautiful that they are admired, but it's a shame because there are still many people who don't know what the real name of the door is. which they are familiar with the term "traditional Balinese door". If this condition is allowed to drag on, one of the cultural heritage of Bali may become extinct. Realizing the above conditions, through the momentum of Nangun Sat Kerti Loka Bali, the local government of Bali is trying to preserve local culture so that it is not uprooted from its original values. Research methods: The research method used is interpretive qualitative. Etymologically, qualitative comes from quality which means value. Findings: As a traditional door Kori Kuwadi has a unique thing that makes many people interested. Kori Kuwadi is used as an architectural part this day it is not placed only at holly place in Bali but as an entrance of the modern building. Implications: Aesthetic aspect does not come from one thing but can be anything. Pintu Kuwadi has its authentic beauty that comes from history, ornament pattern, material, and measurement.